Role of Antigravity Training in Rehabilitation and Return to Sport After Running Injuries - Heather K. Vincent, M.D., Ph.D; Aimee Madsen, M.D; Kevin R. Vincent, M.D., Ph.D (Elsevier, 2022)
Abstract: Anti-gravity treadmill training is a therapeutic option to help recovering runners return to activity after injury. This current concept paper provides a synopsis of the latest evidence of the biomechanical and metabolic changes that occur with body weight support (BWS) treadmill training, effects of antigravity treadmill training on clinical outcomes and clinical case studies in injured runners. Literature searches identified studies with descriptive, experimental and interventional designs and case studies that examined acute and chronic use of antigravity treadmills in runners and relevant populations. Laboratory-based studies were included to provide technical considerations for rehabilitation programming. Antigravity treadmills use causes reductions in cadence, ground reaction forces (GRF), GRF impulses, knee and ankle range of motion, and vertical stiffness, with elevations in stride duration, flight time, ground contact time, and plantarflexion. Antigravity treadmills appear useful across a spectrum of injuries in runners, including postsurgical repair of osteochondral defect, stress reactions (medial tibia, pelvis), and lumbar disc herniation. Runners may preserve aerobic fitness, muscle activation patterns, and muscle mass during recovery compared to traditional rehabilitation protocols. Technical considerations for accurate loading include treadmill frame adjustment to appropriate height to ensure accuracy of level of BWS while running, and monitoring for fast cadence to ensure impact loading rates remain low. Speed or grade can be increased to maintain metabolic demand and fitness while minimizing bone and tissue loading. Monitoring for symptom provocation will guide protocol adjustments to BWS and prescriptions. Once able to run pain-free (sustained or interval) >95% BWS for >30 min, the runner is likely ready to safely transition to ground running. Antigravity treadmill training can be considered when available to facilitate smooth transition back to ground running in a conditioned state.